THE EFFECT OF PRICE DISCOUNTS ON CUSTOMER SATISFACTION WITH IN STORE DISPLAY AS AN INTERVENING VARIABLE (Case Study on Rizky Net Bandar Masilam Customers Simalungun Regency) - Adnan; Asy'ari Nisyullah; Zahrul Fuadi; Ikram (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In this study, the population was employees of the Ministry of Marine Transportation, Serdang Bedagai Regency, 32 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population, totaling 32 employees of the Ministry of Marine Transportation, Serdang Bedagai Regency, will be used as the research sample. Research results. the first hypothesis is accepted, meaning that Job Training (X) has a significant effect on Organizational Commitment (Y1). the second hypothesis is accepted, meaning that Job Training (X) has a significant effect on Job Performance (Y2). the third hypothesis is rejected, meaning that Organizational Commitment (Y1) is not an intervening variable that mediates the effect of Job Training (X) on Job Performance (Y2).